Maize silage as sole forage source for dairy cows in small-scale systems in the highlands of central Mexico - JAIMEZ-GARCÍA, A S; HEREDIA-NAVA, D; ESTRADA-FLORES, J G; VICENTE, F; MARTÍNEZ-FERNÁNDEZ, A; LÓPEZ-GONZÁLEZ, F; ARRIAGA-JORDÁN, C M (The Indian Journal of Animal Sciences, 2017)
Present study was undertaken to evaluate forage options for dairy cows in small-scale dairy systems under lower availability of water for irrigation, using maize silage as sole forage or grazed cultivated pasture plus maize silage. Two groups of 5 Holstein cows balanced in live-weight, parity and days in milk were formed. The productive and economic performance of treatment T1 that received a diet of maize silage (12.8 kg DM/cow/day) plus 3.5 kg/day of a high protein concentrate (71% soyabean meal and 29% ground maize grain) was compared with treatment T2 of grazed ryegrass-white clover irrigated pasture for 8 h/day, 8.1 kg DM/cow/day of maize silage and 5.0 kg of commercial concentrate with 18% CP. The experiment lasted for 11 weeks. Milk yields were 19.2 and 17.1 kg/cow/day for T1 and T2. There were no significant differences for milk fat or protein content, live-weight or body condition score. Although total feeding costs were higher in T1 (4%), the slightly higher milk yield resulted in a cost per litre 10.5% less in T1; representing 7% higher returns/feeding cost ratio. T1 is an option in future scenarios of scarce water for irrigation and for small-scale dairy farmers without access to irrigation.